2013
DOI: 10.1111/tri.12148
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal growth on an everolimus- versus an MMF-based steroid-free immunosuppressive regimen in paediatric renal transplant recipients

Abstract: SummaryConcerns have been raised that mammalian target of rapamycin inhibitors in pediatric transplant recipients might interfere with longitudinal bone growth by inhibition of growth factor signaling and growth plate chondrocyte proliferation. We therefore undertook a prospective nested, case-control study on longitudinal growth over 2 years in steroid-free pediatric renal transplant recipients. Fourteen patients on a steroid-free maintenance immunosuppressive regimen consisting of low-dose everolimus (EVR) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Longitudinal growth, based on the change in height z‐scores, and sexual maturation were unaffected by the introduction of everolimus. It is possible that over longer‐term follow‐up steroid withdrawal in the EVR/rTAC cohort might lead to an improved longitudinal growth but this was not observed in the short 6‐month window between initiation of steroid discontinuation and the end of the current observation period.…”
Section: Discussionmentioning
confidence: 94%
“…Longitudinal growth, based on the change in height z‐scores, and sexual maturation were unaffected by the introduction of everolimus. It is possible that over longer‐term follow‐up steroid withdrawal in the EVR/rTAC cohort might lead to an improved longitudinal growth but this was not observed in the short 6‐month window between initiation of steroid discontinuation and the end of the current observation period.…”
Section: Discussionmentioning
confidence: 94%
“…Also longitudinal growth was comparable between the groups; but these data are difficult to interpret, because the percentage of steroid-free and growth-hormone treated patients was different between the two groups. We previously reported that longitudinal growth over 2 years in steroid-free pediatric patients on low-dose EVR and CsA is not different to that of a matched steroid-free control group on an immunosuppressive regimen with standard-dose CNI and MMF [ 23 ]. Hence, low-dose EVR does not appear to negatively impact longitudinal growth in pediatric renal transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…No change in sex hormone levels occurred in more recent trials of everolimus in children which used lower immunosuppressant doses [94]. There is some evidence that everolimus in combination with low-dose CNIs does not have a negative effect on growth in pediatric transplant patients [95,96]. In terms of sirolimus, albeit in combination with standard-exposure CNIs, case and case-control studies have reported mixed results of either negative or no effects [94].…”
Section: Comparison Of Sirolimus and Everolimus In Clinical Trialsmentioning
confidence: 99%